Uniting a Broken Nation: A Study of the Unification Devices Employed by Antebellum Baptist Ministers in the American Slavery Debate - Coelho, Catherine (Wake Forest University, 2012)
This thesis explores the unification devices employed by two antebellum Baptist ministers in the American slavery debate. By analyzing the published correspondence between Rev. Francis Wayland of New England and Rev. Richard Fuller of South Carolina it is noted that their focus on charity throughout their debate allows them to effectively promote and demonstrate unity to a fragmented national audience. It becomes clear that their reliance on charity, much akin to Augustine's rule of charity, is the fundamental tool that allows the men to harmonize otherwise irreconcilable differences. Specifically identified in this study are the men's similar biblically-based argumentative strategies, their interpretive reliance on charity, and their explicit incorporation of charity into their correspondence with one another and their audience. Granting significance to these identifications are the parallel connections made between antebellum arguments and contemporary religious-political debates which continually beget national and religious dissonance.
Keywords: American; Antebellum; Baptist; Fuller; Slavery; Wayland